All hard X-ray transient grating spectroscopy - Ferrari, Eugenio; Ueda, Hiroki; Fainozzi, Danny; Osaka, Taito; Bencivenga, Filippo; Burian, Max; Carrara, Pietro; Vila-Comamala, Joan; Cucini, Riccardo; David, Christian; Gessini, Alessandro; Gerber, Simon; et al. (Communications physics, 2025)
Optical-domain transient grating (TG) spectroscopy is the ideal tool to investigate transport phenomena in gases, liquids and solids, but it is limited to typically micron-size grating periods. Extreme-Ultraviolet TG has represented a major leap forward to access the mesoscopic scales. Hard X-ray TGs open access in principle to the nanoscale. Hard X-ray TGs were recently generated using the Talbot effect and probed by optical pulses, but these hinder exploiting the advantages of the nanoscale gratings. Here, we present an all-X-ray TG study, in which few-femtosecond hard X-ray pulses are used both for excitation and probing. Our experiment was performed on an amorphous film of an FeGd alloy and on a thin silicon single crystal. The results show a manifestation of the TG induced by the X-ray pump and probe pulses in the form of Talbot carpets, as well as temporal evolution of the grating in crystalline silicon showing coherent optical phonons. Ultrafast all-X-ray TG spectroscopy has the potential to study fundamental excitations with femtosecond time resolution and nanometer spatial sensitivity. Using hard X-rays for transient grating (TG) spectroscopy, fundamental excitations can be followed with femtosecond temporal and nanometer spatial resolution, selecting momenta, chemical elements and their chemical environment. The authors demonstrate the first experiment of all X-ray TG on an amorphous film of FeGd and on a silicon single crystal.